Psychophysiological bases of gnoseogenesis - Santibáñez Hidalgo, Guy (Revista de Psicología, 2001)
Gnoseogenesis is the process that leads to the production of knowledge, either empirical or epistemic.The genesis of knowledge is a result of a series of dynamic interactions. The best known is the interaction between individuals or groups with the environment to which the gnostic objects belong.The genesis of knowledge is determined by historical and evolutionary "individual-environment" interactions: the evolution and history of indivual (s)-environment interaction, the history and evolution of the area surrounding the object of the gnostic enquiry, and the history of the individual (s)-object relation of knowledge.Knowledge is a form of plastic activity (learning), based on a complex structuration of subjective and behavioural functions. These functions are in intimate interaction through time and space, and are generated by the integrative functions of the Neuroendocrine System (NES): excitability, plasticity and subjectivity.Subjectivity is responsible for the virtuality of the process, behaviour for its operability and both are responsible for prediction and anticipation.Thus, it is possible to formulate a conceptual descriptive proposition according to which it may be convenient to clarify that knowledge is a psychological process.So far as knowledge increases, the NES (Neuroendocrine system) inhibits the consciousness of the process in order to allow it to become automatic. The change of level in the creation of knowledge implies a parallel course of both forms of function.